The relationship between Helicobacter pylori infection and depressive symptoms in the general population in China: The TCLSIH cohort study. Issue 5 (22nd July 2019) - Gu, Yeqing; Zheng, Lixiao; Kumari, Shubham; Zhang, Qing; Liu, Li; Meng, Ge; Wu, Hongmei; Bao, Xue; Yao, Zhanxin; Sun, Shaomei; Wang, Xing; Zhou, Ming; et al.
Abstract: Background: Depressive symptoms are a common, debilitating, and costly public health issue. Helicobacter pylori ( H pylori ) infection cause changes in the normal physiological state of the gastrointestinal (GI) flora. Although the physiological state of the GI tract is closely related to mental disorders, few population studies have examined the relationship between H pylori infection and depressive symptoms in the general population. The aim of this study was to examine whether H pylori infection is related to depressive symptoms among the general adult population. Materials and Methods: This cross‐sectional study included 5558 inhabitants of Tianjin, China. H pylori infection was diagnosed with the carbon 13 breath test. Depressive symptoms were assessed using the Chinese version of 20‐item Self‐rating Depression Scale (SDS) with three cutoffs (45, 48, and 50) to indicate elevated depressive symptoms. Multiple logistic regression analysis were conducted to assess the association between H pylori infection and depressive symptoms. Results: The prevalence of depressive symptoms (SDS ≥ 45) was 12.7% in men and 17.4% in women. In multivariable models, the odds ratios and 95% confidence interval of having depressive symptoms by H pylori infection were 1.25 (1.01‐1.56), 1.46 (1.11‐1.91), and 1.46 (1.05‐2.06) for three cutoffs: 45, 48, and 50 in women. However, no significant difference was found between H pylori infection and depressive symptoms in men. Conclusions: This study firstly suggested that H pylori infection was related to depressive symptoms in women in the general adult population. Further prospective studies or randomized trials are required to clarify the causality.